GAMBARAN PENYESUAIAN DIRI SISWA KELAS VIII SMP NEGERI 2 SOREANG - Sarah Nurfauziah; Maya Masyita Suherman (IKIP Siliwangi, 2022)
The background of this research is to find out the description of the adjustment of VIII grade students at SMP Negeri 2 Soreang. This study uses a qualitative approach with a descriptive method. The data collection techniques that I used in this research were interviews and documentation. The primary subjects in this study were BK teachers and class VIII students at SMP Negeri Soreang, while the secondary subjects were homeroom teachers for class VIII A. The results of the research conducted on the four students at SMP Negeri 2 Soreang showed that the four students had low self-adjustment. The factors and causes of the four students' low self-adjustment are different, but the classroom environment is the main point in the four students' self-adjustment.